The Cambridge companion to Christian mysticism - Hollywood, Amy M., 1963-; Beckman, Patricia Z., 1967- (Cambridge companions to religion., 2012)
The Cambridge Companion to Christian Mysticism is a multi-authored interdisciplinary guide to the study of Christian mysticism, with an emphasis on the third through the seventeenth centuries. This book looks beyond the term 'mysticism', which was an early modern invention, to explore the ways in which the ancient terms 'mystic' and 'mystical' were used in the Christian tradition: what kinds of practices, modes of life and experiences were described as 'mystical'? What understanding of Christianity and of the life of Christian perfection is articulated through mystical interpretations of scripture, mystical contemplation, mystical vision, mystical theology or mystical union? This volume both provides a clear introduction to the Christian mystical life and articulates a bold new approach to the study of mysticism.